Bagaimana Faktor Produk Ramah Lingkungan dan Promosi Ramah Lingkungan yang Perlu Dipertimbangkan dalam Keputusan Pembelian? - Rachmi Amalia; Bagas Pratama; Ali Komarudin; Soesanty Maulany (CV. AFDIFAL MAJU BERKAH, 2024)
Preserving the environment and maintaining health are shared responsibilities. A robust immune system and overall good health are essential for everyone. Health is fundamental to carrying out daily life effectively. While a strong immune system is crucial, maintaining other bodily functions is equally important for optimal well-being. These efforts are crucial not only for enhancing quality of life but also for preventing global warming. Therefore, this study examines the influence of green products and green promotions on consumer purchase decisions. Employing a quantitative approach with an explanatory method, the research involved 224 Tropicana Slim consumers in Yogya Junction, Cirebon City, who had purchased the product at least once. Data were analyzed using the structural equation modeling (SEM) approach with the partial least squares (PLS) method. The findings indicate that green products and green promotions significantly impact consumer purchase decisions. As evidenced by the test results (t-value for Green Product > 6.722, p-value < 0.000; t-value for Green Promotion > 4.923, p-value < 0.000), both hypotheses are supported. This confirms that green products and green promotions positively influence purchasing decisions. We expect future research with a broader sample and more robust methodologies to strengthen these findings.